2015
DOI: 10.1063/1.4922697
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the electric-dipole approximation: A formulation and implementation of molecular response theory for the description of absorption of electromagnetic field radiation

Abstract: Beyond the electric-dipole approximation: A formulation and implementation of molecular response theory for the description of absorption of electromagnetic field radiation, 2015, Journal of Chemical Physics, (142) We present a formulation of molecular response theory for the description of a quantum mechanical molecular system in the presence of a weak, monochromatic, linearly polarized electromagnetic field without introducing truncated multipolar expansions. The presentation focuses on a description of line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 63 publications
2
95
0
Order By: Relevance
“…The problems associated with origin dependence can be overcome by switching from the length to the velocity representation or even more elegantly to the exact expression as presented by List et al [23]. The List et al [23] approach also avoids the unphysical total negative intensities observed in [27] in the velocity representation and in the length representation in this work irrespectively of the choice of basis set.…”
Section: [(Hedta)feofe(hedta)]mentioning
confidence: 81%
See 2 more Smart Citations
“…The problems associated with origin dependence can be overcome by switching from the length to the velocity representation or even more elegantly to the exact expression as presented by List et al [23]. The List et al [23] approach also avoids the unphysical total negative intensities observed in [27] in the velocity representation and in the length representation in this work irrespectively of the choice of basis set.…”
Section: [(Hedta)feofe(hedta)]mentioning
confidence: 81%
“…The List et al [23] approach also avoids the unphysical total negative intensities observed in [27] in the velocity representation and in the length representation in this work irrespectively of the choice of basis set.…”
Section: [(Hedta)feofe(hedta)]mentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [190] it was demonstrated that the contraction is almost inversely proportional to Z, while the transition energy goes as Z 2 -as expected for hydrogenic systems. This gives a kr depending close to linearly with Z.…”
Section: Short-wavelength Perturbationsmentioning
confidence: 99%
“…The origin-dependent inclusion of higher-order terms in the perturbative field has been developed by Bernadotte et al, 189 and expanded by List et al 190 It has been demonstrated that an origin-independent inclusion of higher-order contributions can be achieved if all contributions to the same order in the wave vector is included consistently. Higher-order terms can break symmetry rules in the dipole approximations, yielding, e.g., 1s → nd transitions.…”
Section: Short-wavelength Perturbationsmentioning
confidence: 99%